Percutaneous kyphoplasty assisted with/without mixed reality technology in treatment of OVCF with IVC: a prospective study - Peiran Wei (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background The purpose of this study was to assess the clinical outcome of percutaneous kyphoplasty (PKP) assisted with mixed reality (MR) technology in treatment of osteoporotic vertebral compression fracture (OVCF) with intravertebral vacuum cleft (IVC). Method Forty cases of OVCF with IVC undergoing PKP were randomized into a MR technology-assisted group (group A) and a traditional C-arm fluoroscopy group (group B). Both groups were performed PKP and evaluated by VAS scores, ODI scores, radiological evidence of vertebral body height, and kyphotic angle (KA) at pre-operation and post-operation. The volume of injected cement, fluoroscopy times, and operation time were recorded. And cases of non-PMMA-endplates-contact(NPEC) in radiological evidence was also recorded postoperatively. The clinical outcomes and complications were evaluated afterwards. All patients received 10 to 14 months follow-up, with an average of 12 months. Result This MR-assisted group (group A) acquired more about the amount of the polymethyl methacrylate (PMMA) injection and postoperative vertebral height and less about postoperative KA, fluoroscopy times, and operation time compared with the control group (group B) (P < 0.05). The VAS scores and ODI scores in both groups have improved, but more significantly in group A (P < 0.05). Also, more cases achieve both-endplates-touching of cement in group A (P < 0.05). And there are less of the loss of vertebral height, KA, and occurrence of re-collapse of the vertebra in group A during the follow-up (P < 0.05). Conclusion PKP assisted with MR technology can accurately orientate the position of IVC area, which can be augmented by the balloon leading to more satisfied vertebral height improvement, cement diffusion, and pain relief. Trial registration ClinicalTrials.gov Identifier: NCT03959059. Registered 25 September 2016.